"Citizen Curation" in Online Discussions of Donald Trump's Presidency: Sharing the News on Mumsnet. Issue 5 (28th May 2018) - Pedersen, Sarah; Burnett, Simon
Abstract : In an era of fake news and concerns about "social-media bubbles", we consider how participants in online discussions on the UK parenting website Mumsnet assess the validity and potential subjectivity of news information sources. Building on previous work on the phenomenon of "social media curation" and "news curation", we argue that there is evidence for the development of a theory and practice of "citizen curation"—the subjective and non-professional collection, assessment and criticism of information by participants in online discussions for the benefit of the group. Participants on Mumsnet collaborate to source, present and curate information from a variety of news sources, and impose a clear hierarchy with reference to these sources' veracity. Information garnered from mainstream, liberal-leaning news sources is given the highest level of trust, often being used to support information from other sources, which are seen as less trustworthy. Information might also be presented from conservative-leaning news sources, but only when it supports the overall anti-Trump tone. Having acknowledged the selective subjectivity of the curatorial process performed by our participants, we then ask how far this contributes to the creation of a "liberal bubble" effect, and how far our participants are willing to go to validate news stories shared in this way. We argue that our participants demonstrated a clear awareness of the veracity and potential subjectivity of their sources, worked collaboratively to verify news items, and were proud of their ability to "scoop" the mainstream news media on occasion. Given that earlier work on such groups of news-absorbed users has suggested that they tend to be male, the identification of such a group on a female-dominated website also expands the literature and suggests that such gender differentiations should be made with care.